Pengaruh Kualitas Produk dan Harga Terhadap Kepuasan Pembelian Mie Gacoan di Gofood (Studi Kasus pada Mahasiswa Fakultas Ekonomi di Unusida) - Thalita Al Faustina; Yolanda Irma Zunita; Edita Rachma Kamila (Universitas Kristen Indonesia Toraja, 2025)
This study aims to analyze the impact of product quality and price on consumer satisfaction in purchasing Mie Gacoan through the GoFood platform. Using a quantitative method with the Partial Least Square (PLS) approach, data were collected from 75 respondents selected through purposive sampling. The findings reveal that both product quality and price positively and significantly influence consumer satisfaction, with product quality having a stronger effect than price. These results suggest that Mie Gacoan's management should focus on enhancing product quality and offering competitive pricing to maintain consumer satisfaction and loyalty.